Distorsions dans les interactions entre adultes et enfants - Miehakanda M’Badi (Éducation et Socialisation)
This approach of adult and child interactions takes place in theories of language acts, with object ethologic observing and pragmatic analyzing of language practices crossed by interactional distortions.